The Nine-Hole Peg Test as a manual dexterity performance measure for multiple sclerosis. (April 2017) - Feys, Peter; Lamers, Ilse; Francis, Gordon; Benedict, Ralph; Phillips, Glenn; LaRocca, Nicholas; Hudson, Lynn D; Rudick, Richard; ,
Impaired manual dexterity is a frequently reported disability in people with multiple sclerosis (MS) and is increasingly prevalent with worsening disease. While various tests and patient-reported outcome measures are available, the Nine-Hole Peg Test (NHPT) is considered as a gold standard measure of manual dexterity and most frequently used in MS research and clinical practice. The MS Outcome Assessments Consortium (MSOAC) includes representatives from advocacy organizations, Food and Drug Administration (FDA), European Medicines Agency (EMA), National Institute of Neurological Disorders and Stroke (NINDS), academic institutions, and industry partners along with persons living with MS. Among the MSOAC goals are acceptance and qualification by regulators of performance outcomes that are highly reliable and valid, practical, cost-effective, and meaningful to persons with MS. A critical step for these neuroperformance metrics is elucidation of clinically relevant benchmarks, well-defined degrees of disability, and gradients of change that are deemed clinically meaningful. This article addresses the NHPT, the proposed MSOAC measure for upper extremity function. We find that the NHPT is reliable within and between test sessions, discriminates between healthy subjects and MS patients with different levels of upper limb impairment, and shows high convergent validity with other manual dexterity as well as more comprehensive upper limb measures. Ecological validity is established by its relation to perceived upper limb use in daily life and perceived difficulty in performing activities of daily living. The NHPT is responsive to deterioration in longitudinal studies, and research suggests that a 20% change in test score is commonly used to define clinically meaningful worsening, a definition that needs further validation in all stages of the disease.